Virginia Woolf and the study of nature - Alt, Christina, 1976- (Cambridge, UK. : Cambridge University Press, 2010)
'Reflecting the modernist fascination with science, Virginia Woolf's representations of nature are informed by a wide-ranging interest in contemporary developments in the life sciences. Christina Alt analyses Woolf's responses to disciplines ranging from taxonomy and the new biology of the laboratory to ethology and ecology and illustrates how Woolf drew on the methods and objectives of the contemporary life sciences to describe her own literary experiments. Through the examination of Woolf's engagement with shifting approaches to the study of nature, this work covers new ground in Woolf studies and makes an important contribution to the understanding of modernist exchanges between literature and science'--
Includes bibliographical references and index.
Keywords: Woolf, Virginia, -- 1882-1941 -- Criticism and interpretation; Woolf, Virginia, -- 1882-1941 -- Knowledge -- Natural history; Woolf, Virginia, -- 1882-1941 -- Knowledge -- Life sciences; Nature in literature; Life sciences in literature; Life sciences -- United Kingdom -- History -- 19th century; Life sciences -- United Kingdom -- History -- 20th century; Literature and science -- United Kingdom -- History -- 20th century